(untitled) (Environment & Health, 2023)
The 3RIVE 3D pesticide application system, developed by FMC and Micro-Trak Systems Inc., allows to reduce the amount of pesticides used increasing their effectiveness. This innovative delivery platform converts the traditional high-volume application technology into a low-volume one thanks to the patented technology. The purpose of the work is risk assessment of the bifenthrin influence on the population health when consuming corn grown using the innovative 3RIVE 3D technology. Materials and methods. We calculated the stability indices of bifenthrin (the active ingredient of the Brigade 3Rive 3D, SC formulation) in corn grown using the innovative 3RIVE 3D technology (introduction into the soil with simultaneous sowing of corn seeds). Brigade 3Rive 3D, SC is used as an insecticide on corn crops with a maximum consumption rate of 1.2 l/ha, once. Research results and their discussion. When studying the dynamics of bifenthrin residual amounts in corn grown with the Brigade 3Rive 3D, SC formulation application using 3Rive3D technology, it was established that during the growing season the content of bifenthrin in corn gradually decreased and after 50 days in the ears of corn it was below the limit of quantitative determination of the method. The integral index of hazard when consuming pesticides contaminated food products (IIHCPCF) = ADD+С+ τ50 = 2+2+2 = 6 points (Table 2). That is, according to this index, bifenthrin can be attributed to compounds of the 3rd class of hazard (moderately hazardous compounds), since its moderate toxicity (ADD value) is combined with its moderate resistance in agricultural crops and the relative low corn amount in the diet of Ukrainians. Conclusions. It was established that according to State Standard 8.8.1.002-98 bifenthrin belongs to the 3rd class of hazard – moderately stable compounds. According to the value of integral index of hazard when consuming pesticides contaminated food products bifenthrin can be assigned to the 3rd class of hazard (moderately hazardous compounds). As the application of the Brigade 3Rive 3D, SC formulation using 3Rive3D technology for the protection of corn does not carry the risk of crops pollution and consumption of corn by the population, deterioration of the ecological situation, as well as it has significant agro-economic and population safety advantages, the application of pesticides using 3Rive3D technology is very promising and will be actively and widely implemented in the agricultural practice of Ukraine in the future.